Preparation method and application of polyester
By using titanium dioxide nanotubes as catalysts, the existing polyester catalysts have high toxicity, high cost and easy to cause Maillard reactions, and the efficient and environmentally friendly polyester catalytic effect is achieved.
Patent Information
- Application Number
- CN202411509095.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-25
AI Technical Summary
Existing polyester catalysts have problems such as high toxicity, high cost, and easy to cause Maillard reactions, and titanium catalysts are likely to cause yellowing of the polyester during the polymerization process.
Develop a green, non-toxic titanium polyester catalyst, using titanium dioxide nanotubes as catalyst, and obtaining hydrothermal reaction by adding a modifier to an aqueous alkali solution, for catalyzing the esterification of dicarboxylic acid and diol Reaction and polycondensation reaction.
The synthesis of highly efficient catalytic polyester is achieved, with the catalyst having high activity, good selectivity, low cost and environmentally friendly, avoiding the problems of Maillard reaction and polyester yellowing.
Smart Images

Figure BDA0005104917510000071 
Figure BDA0005104917510000081 
Figure HDA0005104917530000011
Abstract
Description
[Technical field]
[0001] The present application relates to a method for preparing polyester and application thereof, and belongs to the field of polyester catalysts. [Background technology]
[0002] Metal catalysts are widely used catalysts in polyester synthesis. They show excellent catalytic effects in polyester synthesis reactions. The metal sites on the surface are the key to catalysis as Lewis acid catalytic active sites. Dibutyltin oxide, antimony acetate, zirconium isopropoxide, antimony oxide, germanium oxide, isopropyl titanate, tetrabutyl titanate, butyltin tri(octanoate), 2-ethylhexanoic acid tin, stannous oxalate, butyltin acid, aluminum acetylacetonate, etc. all have high catalytic activity in polyester synthesis. However, tin and antimony catalysts have high activity and disadvantages such as high toxicity. However, germanium is scarce and expensive. Titanium catalysts have advantages such as high activity, wide sources, and low cost. However, titanium catalysts are prone to Maillard reaction during polyester polymerization, resulting in yellowing of polyester. Therefore, the development of a low-cost, environmentally friendly catalyst with adjustable catalytic activity is a top priority for the development of the polyester industry. [Summary of the invention]
[0003] Based on the defects of the prior art, the present invention develops a green and non-toxic titanium-based polyester catalyst to achieve catalytic polymerization of polyester.
[0004] [Technical solution]
[0005] According to one aspect of the present application, a method for preparing a polyester catalyst is provided;
[0006] The catalyst is a titanium dioxide nanotube catalyst;
[0007] The titanium dioxide nanotubes are prepared by adding a modifier to a titanium dioxide precursor in an alkaline aqueous solution;
[0008] The alkali in the aqueous alkali solution is selected from any one of alkali metal hydroxides and alkaline earth metal hydroxides, and the modifier is selected from any one of cationic modifiers, anionic modifiers, and zwitterionic modifiers, or a combination of two thereof;
[0009] The polyester is obtained by esterification reaction I and polycondensation reaction I of dicarboxylic acid and diol in a system containing the catalyst. The polyester is obtained by esterification reaction I and polycondensation reaction I of dicarboxylic acid and diol in a system containing the catalyst.
[0010] The titanium dioxide nanotube catalyst has a morphology of TiO2 nanotubes, wherein the tube diameter is 5-10 nm and the tube length is 0.3-1 μm.
[0011] The specific surface area of the titanium dioxide nanotube catalyst is 150 to 1800 m2 / g.
[0012] According to one aspect of the present application, the catalyst is used to catalyze the synthesis of polyester, and the synthesis method of polyester includes:
[0013] The raw materials containing diformic acid and diol are contacted with the activated catalyst to cause esterification reaction I and polycondensation reaction I to obtain the polyester.
[0014] Optionally, the dicarboxylic acid is selected from at least one of terephthalic acid, 2,5-furandicarboxylic acid, 2,5-thiophenedicarboxylic acid, and biphenyldicarboxylic acid.
[0015] Optionally, the diol is selected from at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol and 1,4-cyclohexanedimethanol.
[0016] Optionally, the method for preparing the titanium dioxide precursor comprises the following steps:
[0017] a. Mix titanium salt and anhydrous ethanol, stir mechanically until uniform to obtain a mixed solution, age in an oven at 50-70°C for 1-2 days to form a composite gel, then add 30-80 ml of NaOH with a molar concentration of 10 mol / L, and stir for 60-90 minutes until the mixture is uniformly mixed;
[0018] b. The mixed solution of step a is transferred to a hydrothermal reactor, the reaction temperature is 130-160°C, the reaction time is 24h, the reactor is opened and the upper liquid is decanted, the obtained precipitate is repeatedly washed with deionized water until neutral, and then soaked in a 0.1 mol / L HNO3 solution for 30 minutes, the soaking process is accompanied by mechanical stirring, and then the acid is filtered off, and then washed with deionized water and anhydrous ethanol respectively until neutral, and the product is vacuum dried at a temperature of 60°C for 8h to obtain titanate powder;
[0019] c. Place the powder material in step b in a crucible and sinter at 400° C. for 0.5 h to 1 h under nitrogen or argon atmosphere to obtain a titanium dioxide precursor.
[0020] Optionally, the anions in the titanium source are selected from at least one of nitrate, sulfate, acetate and chloride.
[0021] Optionally, the titanium source comprises organic titanium.
[0022] Optionally, the titanium source is selected from at least one of tetraisopropyl titanate, butyl titanate, and TiCl4.
[0023] Optionally, in the mixed solution, the volume ratio of titanium salt to anhydrous ethanol is 1:15 to 1:30;
[0024] The method for preparing titanium dioxide nanotubes comprises the following steps:
[0025] The titanium dioxide precursor and the modifier are added to the aqueous solution of alkali and stirred until uniform to obtain a mixed solution. The mixed solution is transferred to a hydrothermal reactor, the reaction temperature is 130-160°C, the reaction time is 24 hours, the reactor is opened and the upper liquid is decanted, and the obtained precipitate is repeatedly washed with deionized water and anhydrous ethanol until it is neutral, and the product is vacuum dried at a temperature of 60°C for 8 hours to obtain titanium dioxide nanotube powder;
[0026] The modifier is selected from one or a combination of dodecyldimethylbenzylammonium chloride, dialkyldimethylammonium, dodecyldimethylamine oxide, and tetrabutylammonium hydroxide;
[0027] The alkali in the aqueous alkali solution is selected from any one of potassium hydroxide, sodium hydroxide, barium hydroxide, calcium hydroxide and choline.
[0028] Optionally, the concentration of the aqueous solution of the alkali is 2 mol / L-15 mol / L.
[0029] Optionally, the conditions for activation of the catalyst include:
[0030] Under vacuum, activate at 80-150°C for 2-12 hours.
[0031] Optionally, the esterification reaction I and the polycondensation reaction I are carried out under a nitrogen atmosphere.
[0032] Optionally, in the method for preparing the polyester, the molar amount of the bimetallic MOF catalyst is 0.05‰ to 5‰ of the molar amount of the dibasic acid.
[0033] Optionally, in the method for preparing the polyester, the molar ratio of the dibasic acid to the diol is 1:1.2 to 1:2.5.
[0034] Optionally, the temperature of the esterification reaction I is 180-240°C.
[0035] The time of the esterification reaction I is 1 to 7 hours.
[0036] Optionally, the polycondensation reaction I is carried out under vacuum conditions, with a vacuum degree of <200 Pa,
[0037] The temperature of the polycondensation reaction I is 210-270°C;
[0038] The time of the polycondensation reaction I is 0.5 to 5 hours.
[0039] As a specific implementation, the preparation method of the titanium dioxide nanotube catalyst is:
[0040] The titanium dioxide precursor and the modifier are dissolved in an aqueous solution of alkali, mechanically stirred to obtain a homogeneous reaction solution, and then subjected to a hydrothermal reaction to obtain the titanium dioxide nanotube catalyst.
[0041] The polymerization method of the polyester is:
[0042] The titanium dioxide nanotube catalyst is contacted with diformic acid and diol to synthesize the polyester by direct esterification;
[0043] [Beneficial Effects]
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] (1) The titanium dioxide nanotube catalyst provided in the present application has the ability to efficiently catalyze the synthesis of polyester.
[0046] (2) The titanium dioxide nanotube catalyst is a green, low-cost polyester catalyst with the advantages of high activity, good selectivity and universal applicability.
Brief Description of the Drawings
[0047] Figure 1 This is a scanning electron microscope photograph of the titanium dioxide nanotubes in Preparation Example 1.
[0048] Figure 2 This is a transmission electron microscope photograph of the titanium dioxide nanotubes in Preparation Example 1.
[0049] Figure 3 This is the N2 isothermal adsorption-desorption curve of the titanium dioxide nanotubes in Preparation Example 1. [Specific implementation method]
[0050] The following is further described in conjunction with the accompanying drawings, which does not limit the scope of the present invention.
[0051] Preparation Example 1
[0052] Titanium dioxide precursor: titanium chloride and anhydrous ethanol are mixed, mechanically stirred until uniform to obtain a mixed solution, aged in an oven at a temperature of 70°C for 1 day to form a composite gel, and then 30ml of NaOH with a molar concentration of 10mol / L is added, and stirred for 60-90 minutes until the mixture is uniformly mixed; the mixed solution is transferred to a hydrothermal reactor, the reaction temperature is 130-160°C, the reaction time is 24h, the reactor is opened to decant the upper liquid, and the resulting precipitate is repeatedly washed with deionized water until neutral, and then soaked in 30ml of HNO3 solution with a volume concentration of 0.1mol / L for 30 minutes, the soaking process is accompanied by mechanical stirring, and then the acid solution is filtered off, and then washed with deionized water and anhydrous ethanol respectively until neutral, the product is vacuum dried at a temperature of 60°C for 8h to obtain a titanate powder; the powder material is placed in a crucible, and sintered at a temperature of 400°C for 0.5h-1h under the protection of nitrogen or argon atmosphere to obtain a titanium dioxide precursor. Among them, titanium chloride: anhydrous ethanol = 1:25 (volume ratio)
[0053] Titanium dioxide nanotubes: At room temperature, add titanium dioxide precursor and dodecyldimethylbenzylammonium chloride to an aqueous alkaline solution and stir until uniform to obtain a mixed solution. Move the mixed solution to a hydrothermal reactor. The reaction temperature is 130-160°C and the reaction time is 24 hours. After opening the reactor and decanting the upper liquid, the resulting precipitate is repeatedly washed with deionized water and anhydrous ethanol until it is neutral. The product is vacuum dried at 60°C for 8 hours to obtain titanium dioxide nanotube powder; wherein, titanium dioxide precursor: tetrabutylammonium hydroxide = 1:4 (molar ratio).
[0054] Preparation Example 2
[0055] Titanium dioxide precursor: titanium chloride and anhydrous ethanol are mixed, mechanically stirred until uniform to obtain a mixed solution, aged in an oven at a temperature of 70°C for 1 day to form a composite gel, and then 30ml of NaOH with a molar concentration of 10mol / L is added, and stirred for 60-90 minutes until the mixture is uniformly mixed; the mixed solution is transferred to a hydrothermal reactor, the reaction temperature is 130-160°C, the reaction time is 24h, the reactor is opened to decant the upper liquid, and the resulting precipitate is repeatedly washed with deionized water until neutral, and then soaked in 30ml of HNO3 solution with a volume concentration of 0.1mol / L for 30 minutes, the soaking process is accompanied by mechanical stirring, and then the acid solution is filtered off, and then washed with deionized water and anhydrous ethanol respectively until neutral, the product is vacuum dried at a temperature of 60°C for 8h to obtain a titanate powder; the powder material is placed in a crucible, and sintered at a temperature of 400°C for 0.5h-1h under the protection of nitrogen or argon atmosphere to obtain a titanium dioxide precursor. Among them, titanium chloride: anhydrous ethanol = 1:25 (volume ratio)
[0056] Titanium dioxide nanotubes: At room temperature, add titanium dioxide precursor and tetrabutylammonium hydroxide to an aqueous alkaline solution and stir until uniform to obtain a mixed solution. The mixed solution is transferred to a hydrothermal reactor. The reaction temperature is 130-160°C and the reaction time is 24 hours. After opening the reactor and decanting the upper liquid, the resulting precipitate is repeatedly washed with deionized water and anhydrous ethanol until it is neutral. The product is vacuum dried at 60°C for 8 hours to obtain titanium dioxide nanotube powder; wherein, titanium dioxide precursor: ammonium hydroxide = 1:8 (molar ratio).
[0057] Preparation Example 3
[0058] Titanium dioxide precursor: titanium chloride and anhydrous ethanol are mixed, mechanically stirred until uniform to obtain a mixed solution, aged in an oven at a temperature of 70°C for 1 day to form a composite gel, and then 30ml of NaOH with a molar concentration of 10mol / L is added, and stirred for 60-90 minutes until the mixture is uniformly mixed; the mixed solution is transferred to a hydrothermal reactor, the reaction temperature is 130-160°C, the reaction time is 24h, the reactor is opened to decant the upper liquid, and the resulting precipitate is repeatedly washed with deionized water until neutral, and then soaked in 30ml of HNO3 solution with a volume concentration of 0.1mol / L for 30 minutes, the soaking process is accompanied by mechanical stirring, and then the acid solution is filtered off, and then washed with deionized water and anhydrous ethanol respectively until neutral, the product is vacuum dried at a temperature of 60°C for 8h to obtain a titanate powder; the powder material is placed in a crucible, and sintered at a temperature of 400°C for 0.5h-1h under the protection of nitrogen or argon atmosphere to obtain a titanium dioxide precursor. Among them, titanium chloride: anhydrous ethanol = 1:25 (volume ratio)
[0059] Titanium dioxide nanotubes: At room temperature, add titanium dioxide precursor and tetrabutylammonium bromide to an aqueous alkaline solution and stir until uniform to obtain a mixed solution. The mixed solution is transferred to a hydrothermal reactor. The reaction temperature is 130-160°C and the reaction time is 24 hours. After opening the reactor and decanting the upper liquid, the resulting precipitate is repeatedly washed with deionized water and anhydrous ethanol until it is neutral. The product is vacuum dried at 60°C for 8 hours to obtain titanium dioxide nanotube powder; wherein, titanium dioxide precursor: hexabutylammonium hydroxide = 1:8 (molar ratio).
[0060] Example 1
[0061] 0.1 mol of terephthalic acid and 0.14 mol of ethylene glycol were used as raw materials (the molar ratio of alcohol to acid was 1.4), the titanium dioxide nanotubes synthesized in Preparation Example 1 were used as catalyst, the amount of titanium dioxide nanotubes was 0.5‰ of the molar amount of terephthalic acid, the esterification reaction was carried out under nitrogen protection, esterification was carried out at 180°C to 240°C for 5h, and the condensation reaction was stopped at 260°C for 2h under vacuum conditions. The condensation product PET1 was tested for color and viscosity. The results are shown in Table 1.
[0062] Example 2
[0063] 0.1 mol of 2,5-furandicarboxylic acid and 0.16 mol of ethylene glycol were used as raw materials (the molar ratio of alcohol to acid was 1.4), the titanium dioxide nanotubes synthesized in Preparation Example 2 were used as catalysts, the amount of titanium dioxide nanotubes used was 0.5‰ of the molar amount of 2,5-furandicarboxylic acid, the esterification reaction was carried out under nitrogen protection, the esterification was carried out at 200°C for 2.5h, and the condensation reaction was stopped at 230°C for 3h. The obtained product, polyethylene 2,5-furandicarboxylate PEF2, was tested for color and viscosity. The results are shown in Table 1.
[0064] Example 3
[0065] 0.1 mol of terephthalic acid and 0.14 mol of ethylene glycol were used as raw materials (the molar ratio of alcohol to acid was 1.4), the titanium dioxide nanotubes synthesized in Preparation Example 3 were used as catalyst, the amount of titanium dioxide nanotubes was 0.5‰ of the molar amount of terephthalic acid, and the esterification reaction was carried out under nitrogen protection, esterification at 180°C to 240°C for 5h, and the condensation reaction was stopped at 260°C for 2h. The condensation product PET3 obtained was tested for color and viscosity. The results are shown in Table 1.
[0066] Example 4
[0067] 0.1 mol of 2,5-furandicarboxylic acid and 0.16 mol of ethylene glycol were used as raw materials (molar ratio of alcohol to acid was 1.5), titanium dioxide nanotubes synthesized in Preparation Example 1 were used as catalyst, the amount of titanium dioxide nanotubes used was 0.5‰ of the molar amount of 2,5-furandicarboxylic acid, esterification reaction was carried out under nitrogen protection, esterification was carried out at 200°C for 2.5h, and condensation reaction was carried out at 230°C for 3h to stop the reaction. The color and viscosity of the obtained product PEF4 were tested. The results are shown in Table 1.
[0068] Example 5
[0069] 0.1 mol of terephthalic acid and 0.14 mol of ethylene glycol were used as raw materials (the molar ratio of alcohol to acid was 1.6), the titanium dioxide nanotubes synthesized in Preparation Example 1 were used as catalyst, the amount of titanium dioxide nanotubes was 0.5‰ of the molar amount of terephthalic acid, and the esterification reaction was carried out under nitrogen protection, esterification at 180°C to 240°C for 5h, and the condensation reaction was stopped at 260°C for 2h. The condensation product PET5 was tested for color and viscosity. The results are shown in Table 1.
[0070] Example 6
[0071] 0.1 mol of 2,5-furandicarboxylic acid and 0.16 mol of ethylene glycol were used as raw materials (the molar ratio of alcohol to acid was 1.4), the titanium dioxide nanotubes synthesized in Preparation Example 1 were used as catalyst, the amount of titanium dioxide nanotubes used was 0.25‰ of the molar amount of 2,5-furandicarboxylic acid, the esterification reaction was carried out under nitrogen protection, the esterification was carried out at 200°C for 2.5h, and the condensation reaction was stopped at 230°C for 3h. The color and viscosity of the obtained product PEF6 were tested. The results are shown in Table 1.
[0072] Example 7
[0073] 0.1 mol of terephthalic acid and 0.14 mol of ethylene glycol were used as raw materials (the molar ratio of alcohol to acid was 1.4), the titanium dioxide nanotubes synthesized in Preparation Example 1 were used as catalyst, the amount of titanium dioxide nanotubes used was 1‰ of the molar amount of terephthalic acid, and the esterification reaction was carried out under nitrogen protection, esterification at 180°C to 240°C for 5h, and the condensation reaction was stopped at 260°C for 2h. The condensation product PET7 was tested for color and viscosity. The results are shown in Table 1.
[0074] Example 8
[0075] 0.1 mol of terephthalic acid and 0.14 mol of ethylene glycol were used as raw materials (the molar ratio of alcohol to acid was 1.4), titanium dioxide nanotubes were used as catalysts, and the amount of titanium dioxide nanotubes was 0.25‰ of the molar amount of terephthalic acid. The esterification reaction was carried out under nitrogen protection, esterification at 180°C to 240°C for 5h, and the condensation reaction was stopped at 260°C for 2h. The condensation product PET8 was tested for color and viscosity. The results are shown in Table 1.
[0076] Comparative Example 1
[0077] 0.1 mol of terephthalic acid and 0.14 mol of ethylene glycol were used as raw materials (the molar ratio of alcohol to acid was 1.4), tetrabutyl titanate was used as a catalyst, and the amount of tetrabutyl titanate was 0.5‰ of the molar amount of terephthalic acid. The esterification reaction was carried out under nitrogen protection, esterification at 180°C to 240°C for 5h, and the condensation reaction was stopped at 260°C for 2h. The condensation product PET1D was tested for color and viscosity. The results are shown in Table 1.
[0078] Comparative Example 2
[0079] 0.1 mol of terephthalic acid and 0.14 mol of ethylene glycol were used as raw materials (the molar ratio of alcohol to acid was 1.4), titanium dioxide (commercial product) was used as a catalyst, and the amount of titanium dioxide (commercial product) was 0.5‰ of the molar amount of terephthalic acid. The esterification reaction was carried out under nitrogen protection, esterification at 180°C to 240°C for 5h, and the polycondensation reaction was stopped at 260°C for 2h. The condensation product PET2D obtained was tested for color and viscosity. The results are shown in Table 1.
[0080] Table 1
[0081]
[0082]
[0083] According to Table 1, the titanium dioxide nanotube catalyst has a high catalytic activity for catalyzing the polymerization of diacids and diols, and the intrinsic viscosity of the obtained polyester is much higher than that of the traditional titanium polyester catalyst tetrabutyl titanate, and the color is very good, and the b value is low, all lower than 2.5. From Comparative Example 1, it can be seen that although the traditional titanium polyester catalyst tetrabutyl titanate can catalyze the polymerization reaction, it has a low depolymerization activity for polyester, and the color of the obtained polyester is very yellow, which is a caramel color. From Comparative Example 2, it can be seen that although the titanium dioxide (commercial) catalyst can catalyze the polymerization of polyester, the viscosity of the obtained polyester is only 0.22 dL / g, and the activity is very low.
[0084] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing polyester, characterized in that: The polyester includes a catalyst; The catalyst is titanium dioxide nanotubes; The titanium dioxide nanotubes are prepared by adding a modifier to a titanate in an aqueous solution of alkali; The alkali in the aqueous alkali solution is selected from any one of alkali metal hydroxides and alkaline earth metal hydroxides, and the modifier is selected from any one of cationic modifiers, anionic modifiers, and zwitterionic modifiers, or a combination of two thereof; The polyester is obtained by esterification reaction and polycondensation reaction of dicarboxylic acid and diol in a system containing the catalyst.
2. The method for preparing polyester according to claim 1, characterized in that: The titanium dioxide nanotube catalyst has a morphology of TiO2 nanotubes, wherein the tube diameter is 5-10 nm and the tube length is 0.3-1 μm. The specific surface area of the titanium dioxide nanotube catalyst is 150 to 1800 m2 / g.
3. The method for preparing polyester according to claim 1, characterized in that: The raw material containing dicarboxylic acid and diol is contacted with the activated catalyst to cause esterification reaction I and polycondensation reaction I to obtain the polyester. Preferably, the dicarboxylic acid is selected from at least one of terephthalic acid, 2,5-furandicarboxylic acid, 2,5-thiophenedicarboxylic acid, and biphenyldicarboxylic acid; Preferably, the diol is selected from at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol and 1,4-cyclohexanedimethanol.
4. The method for preparing polyester according to claim 1, characterized in that: The preparation method of the titanium dioxide precursor comprises the following steps: a. Mix titanium salt and anhydrous ethanol, stir mechanically until uniform to obtain a mixed solution, age in an oven at 50-70°C for 1-2 days to form a composite gel, then add 30-80 ml of NaOH with a molar concentration of 10 mol / L, and stir for 60-90 minutes until the mixture is uniformly mixed; b. The mixed solution of step a is transferred to a hydrothermal reactor, the reaction temperature is 130-160°C, the reaction time is 24h, the reactor is opened and the upper liquid is decanted, the obtained precipitate is repeatedly washed with deionized water until neutral, and then soaked in a 0.1 mol / L HNO3 solution for 30 minutes, the soaking process is accompanied by mechanical stirring, and then the acid is filtered off, and then washed with deionized water and anhydrous ethanol respectively until neutral, and the product is vacuum dried at a temperature of 60°C for 8h to obtain titanate nanotube powder; c. Place the powder material in step b in a crucible and sinter at 400° C. for 0.5 h to 1 h under nitrogen or argon atmosphere to obtain a titanium dioxide precursor. The method for preparing titanium dioxide nanotubes comprises the following steps: Add the titanium dioxide precursor and modifier to a 10 mol / L alkaline solution and stir until uniform to obtain a mixed solution. Transfer the mixed solution to a hydrothermal reactor. The reaction temperature is 130-160°C and the reaction time is 24 hours. Open the reactor and decant the upper liquid. The resulting precipitate is repeatedly washed with deionized water and anhydrous ethanol until it is neutral. The product is vacuum dried at 60°C for 8 hours to obtain titanium dioxide nanotube powder.
5. The method for preparing nano titanium dioxide nanotubes according to claim 4, characterized in that: The modifier is selected from one or a combination of dodecyldimethylbenzylammonium chloride, dialkyldimethylammonium, dodecyldimethylamine oxide, tetrabutylammonium hydroxide, and tetrabutylammonium bromide; The alkali in the alkaline solution is selected from any one of potassium hydroxide, sodium hydroxide, barium hydroxide, calcium hydroxide and choline.
6. The method for preparing polyester according to any one of claims 1 to 3, characterized in that: The esterification reaction I and the polycondensation reaction I are carried out under a nitrogen atmosphere; Preferably, in the method for preparing the polyester, the molar amount of the nano titanium dioxide catalyst is 0.05‰ to 5‰ of the molar amount of the dibasic acid; Preferably, in the method for preparing the polyester, the molar ratio of the dibasic acid to the diol is 1:1.2 to 1:2.5; Preferably, the temperature of the esterification reaction I is 180-240°C; The time of the esterification reaction I is 1 to 7 hours; Preferably, the polycondensation reaction I is carried out under vacuum conditions with a vacuum degree of <200 Pa. The temperature of the polycondensation reaction I is 210-270°C; The time of the polycondensation reaction I is 0.5 to 5 hours.
Citation Information
Patent Citations
Synthetic method of self-assembly nano titanium dioxide
CN106186053A
Preparation method of polyester
CN113336927A
Method of constructing ultrabiaffinity titanium dioxide nanometer pipe film on metal surface
CN1693540A
The fabrication method of highly crystalline anddispersive photocatalyst of anatase-type titaniumoxide sol by way of hydrothermal treatment
KR1020020043133A
Cited By
Heterometallic MOF-based polyester catalyst as well as preparation method and application thereof
CN121203177A
A heterometallic MOF-based polyester catalyst, its preparation method and application
CN121203177B